Geology and determination of physicochemical parameters of shallow groundwater in and around Kangkong, Pasir Mas, Kelantan - Nurul Suhada Mhd Sukri (2017)
This research is about the geology and determination of physicochemical parameters of groundwater in and around Kangkong, Pasir Mas, Kelantan. The soil analysis and alluvium mapping has been made to determine the distribution of grain size and the type of sediments. The rough review on the distribution of particle size has been made by collected five soil samples from five different localities in this study area. This study area is a flat region and it is composed of Quaternary deposits sediments. The physicochemical parameters which are measured by in-situ are obtained and the water samples which are 15 groundwater samples and one sample from fresh water which was from lake were collected. The samples soon had been undergone several methods to know the concentration of major ions. The major anion concentrations are determined by using the methods such as titration method, gravimetric method, and colorimetric method. While the major cations concentrations are determined by using the Atomic Adsorption Spectrometry (AAS). The concentrations of major ions that have been analyzed were Sodium, Magnesium, Calcium, Iron, Bicarbonate, Chloride, Sulphate and Fluoride. These major ion concentrations and physical parameters can determine the quality of water in the study area. These major cations and major anions have been classified into several groundwater facies using Piper Trilinear Diagram, and Sodium Adsorption Ratio (SAR) graphical method.